Study Of Challenges For Higher Educational Institutions During Covid-19 Pandemic - Thakur, Jagvinder (Gyan Management Journal, 2020)
COVID-19 is a recently discovered strain of coronavirus family that have never seen in human beings  before. Due to its contagious nature or human to human transfer ability, it is ouicially declared as the  worldwide pandemic by World Health Organization. During this pandemic time, it is necessary to shut  down all the human activities to contain the spread and educational institutions are no exception. In  this article, I will highlight some of the key challenges that are being faced by higher educational  institutions while containment of the spread of this virus without disrupting the studies of its students.
Keywords: COVID-19; contagious; online teaching; Higher Education